Development of a framework for genotyping bovine-derived Cryptosporidium parvum, using a multilocus fragment typing tool. Issue 1 (December 2015) - Hotchkiss, Emily; Gilray, Janice; Brennan, Marnie; Christley, Robert; Morrison, Liam; Jonsson, Nicholas; Innes, Elizabeth; Katzer, Frank
Abstract Background There is a need for an integrated genotyping approach forC. parvum ; no sufficiently discriminatory scheme to date has been fully validated or widely adopted by veterinary or public health researchers. Multilocus fragment typing (MLFT) can provide good differentiation and is relatively quick and cheap to perform. A MLFT tool was assessed in terms of its typeability, specificity, precision (repeatability and reproducibility), accuracy and ability to genotypically discriminate bovine-derivedCryptosporidium parvum . Methods With the aim of working towards a consensus, six markers were selected for inclusion based on their successful application in previous studies: MM5, MM18, MM19, TP14, MS1 and MS9. Alleles were assigned according to the fragment sizes of repeat regions amplified, as determined by capillary electrophoresis. In addition, a region of the GP60 gene was amplified and sequenced to determinegp60 subtype and this was added to the allelic profiles of the 6 markers to determine the multilocus genotype (MLG). The MLFT tool was applied to 140C. parvum samples collected in two cross-sectional studies of UK calves, conducted in Cheshire in 2004 (principally dairy animals) and Aberdeenshire/Caithness in 2011 (beef animals). Results Typeability was 84 %. The primers did not amplify tested non-parvum species frequently detected in cattle. In terms of repeatability, within- and between-run fragment sizes showed little variability. Between laboratories, fragment sizes differed but allele calling was reproducible. The MLFT had good discriminatory ability (Simpson's Index of Diversity, SID, was 0.92), compared togp60 sequencing alone (SID 0.44). Some markers were more informative than others, with MS1 and MS9 proving monoallelic in tested samples. Conclusions Further inter-laboratory trials are now warranted with the inclusion of human-derivedC. parvum samples, allowing progress towards an integrated, standardised typing scheme to enable source attribution and to determine the role of livestock in future outbreaks of humanC. parvum .